Improving human resource capacity exploring certification in local governments - Calugay, Zita Concepcion P. (Philippine Journal of Public Administration, 2013)
The proposed institutionalization of certification pathways for local government officers and staff is a step towards the continuing capacity building to raise the qualifications standards and improve the professionalization of the local government bureaucracy. Certification as a concept serves to validate that the local officers and staff possess and are able to demonstrate the required competencies for the job in accordance with set standards, and thus counteract the common perception that they are inefficient, lacking in skills, and hired based on political influence. Two existing and comparable certifications systems, namely, the Technical Education and Skills Development Authority (TESDA) national certification system for technical and vocational skills, and the Local Government Training Package in Australia are analyzed in formulating a model for local government certification system. The proposed local government certification system will require policy reforms geared towards the recognition of the local government sector as an industry and establishment of qualifications framework for the local government industry. Different institutional arrangements or modalities including the centralized, collaborative, privatized, and mixed models may also be explored in pursing the certification system.